Regional Government Public Relations Communication Model in Handling Hoax Information during the Pandemic - Putra, Ruliawan; Fachruddin, Sutiyana (CV. Literasi Indonesia, 2024)
This research aims to describe the management of regional government public relations messages and communication media in handling information hoaxes during the COVID-19 pandemic. The widespread spread of COVID-19 pandemic hoax information has increasingly increased public panic and anxiety, especially in Kendari City. For this reason, the Kendari City Government, through the public relations department, has made various communication efforts to prevent the spread of hoax information. Research data was collected through interviews, observation, and documentation and analyzed using descriptive qualitative data analysis methods to provide a comprehensive picture of the object under study. Research informants were determined using purposive sampling. The results of the research show that the communication model implemented by Kendari City Government Public Relations in preventing COVID-19 pandemic hoaxes is carried out using a participatory communication model using all available communication channels as information media that can be easily accessed by the public. First, by carrying out a thorough identification of the information and hoax news that is being spread. Second, utilizing all types of communication channels available, such as outreach with Regional Apparatus Organizations (OPD) and the community, billboards, collaboration with online news media, partner information service institutions (Kominfo and the Pandemic task force), installing billboards and standing banners, and developing its official website.